Dialogare: compendio di chimica - Peruzzini, Riccardo (Strumenti per la didattica e la ricerca, 2017)
This compendium is aimed at all students who, in the transition from secondary school to university, have to face a chemistry exam in their course of study and want to fill their knowledge gaps or, simply, to review the minimum topics of the subject, before deepening them during university courses. By studying and reviewing the various topics, grouped in parts and units, the reader will therefore have the possibility to access the fundamental notions that make up "General Chemistry". The end-of-chapter exercises are an additional aid allowing students to carry out a self-assessment and, possibly, to identify particularly "difficult" topics to be further studied.